2001
DOI: 10.2337/diacare.24.2.290
|View full text |Cite
|
Sign up to set email alerts
|

Graftskin, a Human Skin Equivalent, Is Effective in the Management of Noninfected Neuropathic Diabetic Foot Ulcers

Abstract: OBJECTIVE— We assessed in a randomized prospective trial the effectiveness of Graftskin, a living skin equivalent, in treating noninfected nonischemic chronic plantar diabetic foot ulcers. RESEARCH DESIGN AND METHODS— In 24 centers in the U.S., 208 patients were randomly assigned to ulcer treatment either with Graftskin (112 patients) or saline-moistened gauze (96 patients, control group). Standard state-of-the-art adjunctive therapy, which included extensive surgical debridement and adequate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
433
3
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 652 publications
(456 citation statements)
references
References 18 publications
13
433
3
7
Order By: Relevance
“…Investigators and industry representatives have advocated many types of wound-care treatments, including wound vacuum-drainage systems [203][204][205][206], recombinant growth factors [207][208][209][210][211][212], skin substitutes [203,[213][214][215][216], antimicrobial dressings [217][218][219], and maggot (sterile larvae) therapy [220][221][222]. Although each treatment likely has some appropriate indications, for infected wounds, available evidence is insufficient to recommend routine use of any of these modalities for treatment or prophylaxis.…”
Section: Treatment Of Infectionmentioning
confidence: 99%
“…Investigators and industry representatives have advocated many types of wound-care treatments, including wound vacuum-drainage systems [203][204][205][206], recombinant growth factors [207][208][209][210][211][212], skin substitutes [203,[213][214][215][216], antimicrobial dressings [217][218][219], and maggot (sterile larvae) therapy [220][221][222]. Although each treatment likely has some appropriate indications, for infected wounds, available evidence is insufficient to recommend routine use of any of these modalities for treatment or prophylaxis.…”
Section: Treatment Of Infectionmentioning
confidence: 99%
“…Data for the percentage of ulcers healed over a period of 12 weeks were obtained from pivotal randomized clinical trials found in the literature. [4][5][6][7][8][9] When the cost for 12 weeks of treatment is divided by the percentage of patients healed in 12 weeks, this gives a cost per 1% patients healed. Using Apligraf as an example in the context of a venous leg ulcer and four applications over 12 weeks, cost for duration of care is $6,816 as determined in first-level calculations.…”
Section: Resultsmentioning
confidence: 99%
“…For skin, several autologous and allogeneic dermal and bi‐layered (epidermis and dermis) constructs have been described over the past years to heal venous and arterial leg ulcers, diabetic foot ulcers and pressure ulcers (Falanga & Sabolinski, 1999; Jones, Nelson, & Al‐Hity, 2013; Kirsner et al, 2012; Marston, Hanft, Norwood, & Pollak, 2003; Veves, Falanga, Armstrong, & Sabolinski, 2001; Wu, Marston, & Armstrong, 2010; Zaulyanov & Kirsner, 2007). Also, application of autologous epidermal cells has been described for treating large burn wounds (Gardien et al, 2016; Gravante et al, 2007; Wood et al, 2012).…”
Section: Introductionmentioning
confidence: 99%